Outbreak of fungemia caused by Candida parapsilosis in a neonatal intensive care unit: Molecular investigation through microsatellite analysis - Da Silva Ruiz, Luciana; Montelli, Augusto Cezar [UNESP]; Sugizaki, Maria de Fátima [UNESP]; Da Silva, Eriques Gonçalves; De Batista, Georgea Carla Matuura; Moreira, Débora; Paula, Claudete Rodrigues (Elsevier, 2013)
Background: Opportunistic infections are an increasingly common problem in hospitals, and the yeast Candida parapsilosis has emerged as an important nosocomial pathogen, especially in neonatal intensive care units (NICUs) where it has been responsible for outbreak cases. Risk factors for C. parapsilosis infection in neonates include prematurity, very low birth weight, prolonged hospitalization, indwelling central venous catheters, hyperalimentation, intravenous fatty emulsions and broad spectrum antibiotic therapy. Molecular methods are widely used to elucidate these hospital outbreaks, establishing genetic variations among strains of yeast. Aims: The aim of this study was to detect an outbreak of C. parapsilosis in an NICU at the Hospital das Clinicas , Faculty of Medicine of Botucatu, a tertiary hospital located in São Paulo, Brazil, using the molecular genotyping by the microsatellite markers analysis. Methods: A total of 11 cases of fungemia caused by C. parapsilosis were identified during a period of 43 days in the NICU. To confirm the outbreak all strains were molecularly typed using the technique of microsatellites. Results: Out of the 11 yeast samples studied, nine showed the same genotypic profile using the technique of microsatellites. Conclusions: Our study shows that the technique of microsatellites can be useful for these purposes. In conclusion, we detected the presence of an outbreak of C. parapsilosis in the NICU of the hospital analyzed, emphasizing the importance of using molecular tools, for the early detection of hospital outbreaks, and for the introduction of effective preventive measures, especially in NICUs. © 2012 Revista Iberoamericana de Micología.
Keywords: Candida parapsilosis; Fungemia; Microsatellite; Neonates; Outbreak; Brazil; candidiasis; clinical article; epidemic; female; fungal strain; fungemia; fungus identification; genotype; human; infant; intensive care unit; male; microsatellite marker; molecular diagnosis; molecular genetics; newborn; newborn intensive care; nonhuman; tertiary health care